A general and rapid room-temperature synthesis approach for metal sulphide nanocrystals with tunable properties. Issue 1 (7th December 2018) - Liu, Yang; Liu, Maixian; Yin, Deqiang; Zhu, Dewei; Swihart, Mark T.
Abstract : A rapid, room-temperature, and solution-phase synthesis produces high-quality, monodisperse metal sulphide nanocrystals with tunable properties. Abstract : Colloidal metal sulphide (MS) nanocrystals (NCs) have recently attracted considerable attention because of their tunable properties that can be exploited in various physical, chemical and biological applications. In this work, we present a novel and general method for synthesis of monodispersed binary (CuS, Ag2 S, CdS, PbS, and SnS), ternary (Ag–In–S, Cu–In–S and Cu–Sn–S) and quaternary (Cu–Zn–Sn–S) MS NCs. The synthesis is conducted at room temperature, with an immediate crystallization process and up to 60 seconds of growth time, enabling rapid synthesis without external heating. For some of the ternary and quaternary NCs produced with relatively low crystallinity, we then carried out a "colloidal annealing" process to improve their crystallinity without changing their composition. Moreover, we show that the morphology and optical properties of the NCs can be tuned by varying the concentration of precursors and reaction time. The shape evolution and photoluminescence of particular MS NCs were also studied. These results not only provide insights into the growth mechanisms of MS NCs, but also yield a generalized, low cost, and potentially scalable method to fabricate them.